A study on the properties of the information model of sustaining the regional economic development by the target program method - Соколова, Надежда Андреевна; Райко, Галина Александровна; Данилец, Евгений Валентинович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper presents the information model of the regional development control through the prism of the integral indicators of strategic programs while involving the target program method of control aimed at balancing social and economic status of the region. The value of the research is based on the fact that the impact of the strategic regional development programs is evaluated by the expenses criterion (as an integral indicator) that helps control the regional budget expenditure. The results of the research are reflected in the paper that presents economic and mathematic models of optimizing expenses on implementing the range of regional programs, with respect to minimizing expenses on the selected multitude of the regional development indicators. The models facilitate optimal management for implementing the range of development programs. Matrix and integral equations of the suggested model help analyse the dynamic change in the regional welfare indices as well as accomplishments in the regional development programs. The paper presents the notion of optimal strategy of the regional development. The strategy is important for eliminating the descriptive development strategies and specifying the managerial aspects of their implementation.